2016
DOI: 10.1021/acs.jpcc.6b07812
|View full text |Cite
|
Sign up to set email alerts
|

Anion Effects on the Solid/Ionic Liquid Interface and the Electrodeposition of Zinc

Abstract: The effect of anions on the solid/ionic liquid (IL) interface and the electrodeposition of zinc have been investigated. The employed ILs are composed of 1-ethyl-3-methyl­imidazolium ([EMIm]+), bis­(trifluoro­methyl­sulfonyl)­imide (TFSI–), trifluoro­methyl­sulfonate (TfO–), methyl­sulfonate (OMs–) and acetate (OAc–). These anions show an increasing cation–anion interaction strength in the order TFSI– < TfO– < OMs– < OAc–, as probed by far-infrared spectroscopy below 200 cm–1. It was shown by in situ AFM that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 43 publications
3
64
0
Order By: Relevance
“…Moreover, the configuration of the anions can also have an impact on the interfacial structure as was addressed, e.g., by Liu et al [ were investigated in contact with the Au (111) surface. AFS measurements under cathodic polarization revealed that the number of layers and force necessary for their punctuation increases systematically with anion size, and it was concluded that this is also the cause for differences in macroscopic electrowetting behavior [97].…”
Section: The Electrified Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the configuration of the anions can also have an impact on the interfacial structure as was addressed, e.g., by Liu et al [ were investigated in contact with the Au (111) surface. AFS measurements under cathodic polarization revealed that the number of layers and force necessary for their punctuation increases systematically with anion size, and it was concluded that this is also the cause for differences in macroscopic electrowetting behavior [97].…”
Section: The Electrified Interfacementioning
confidence: 99%
“…97]. In their work, ionic liquids having the same [EMIm] + cation but four different anions bis(trifluoromethylsulfonyl)imide[TFSI] …”
mentioning
confidence: 99%
“…IL interfaces are particularly important for interface-controlled applications such as sensor [4,[16][17][18][19], lubrication [20][21][22], separation [4,19,[23][24][25][26][27][28][29], electrochemistry [4,19,[30][31][32][33][34][35][36][37][38][39] and electronics [40][41][42] technologies. ILs further stimulated completely new concepts for catalysis [1,4,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…[29] For metal-ion speciation in ILs (or DESs), we refer to ac ritical review by Estager et al and to other relevant articles that are available in the literature. [30][31][32][33][34] The influence of ligands on the asymmetric cleavage and on the nature of the coordination and the number of coordination sites is still required forad etailed understandingo fL CCs. For instance, complexes formed from AlCl 3 and neutral ligands ( 4-propylpyridine or N-butylpyrrolidine) are different upon varying the concentration of AlCl 3 in the mixtures.…”
Section: In [Emim]mentioning
confidence: 99%
“…Corresponding to this bending of the hysteresis curve at high inductions, ar apid increase in high inductionl osses is also found. [32] The bending of the hysteresis curve as well as the high induction losses are controlled by domain-wall nucleation and annihilation processes as well as by rotationo fm agnetic moments. [72][73][74][75] Reasonsf or the in- crease of high induction losses are the presence of non-magnetic pores or non-magnetic inclusions like iron oxidesi nt he deposited material as well as unfavorable orientations of the grains misaligned to the magnetic easy axis.…”
Section: Electrochemical Investigations and Characterization Of The Mmentioning
confidence: 99%